2020
DOI: 10.1192/bjo.2020.2
|View full text |Cite
|
Sign up to set email alerts
|

Intensive support for adults with intellectual disability and behaviours that challenge: a survey of provision and service typologies in England

Abstract: BackgroundApproximately 18% of adults with intellectual disabilities living in the community display behaviours that challenge. Intensive support teams (ISTs) have been recommended to provide high-quality responsive care aimed at avoiding unnecessary admissions and reducing lengthy in-patient stays. AimsTo identify and describe the geographical distribution and characteristics of ISTs, and to develop a typology of IST service models in England. MethodWe undertook a national cross-sectional survey of 73 ISTs. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(40 citation statements)
references
References 20 publications
0
40
0
Order By: Relevance
“…The research team will compare the two models, enhanced provision and independent provision, respectively, of ISTs already identified in phase 1 of the study. 20 The research assistant or clinical study officers will collect study participant-level outcomes at two assessment points (baseline and 9 months) and service-level outcomes over the same time period. The research assistant will also collect qualitative data to understand the experiences and views of key stakeholders, and stakeholder experiences of the different models.…”
Section: Methods and Analysismentioning
confidence: 99%
See 3 more Smart Citations
“…The research team will compare the two models, enhanced provision and independent provision, respectively, of ISTs already identified in phase 1 of the study. 20 The research assistant or clinical study officers will collect study participant-level outcomes at two assessment points (baseline and 9 months) and service-level outcomes over the same time period. The research assistant will also collect qualitative data to understand the experiences and views of key stakeholders, and stakeholder experiences of the different models.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Eight enhanced service provision ISTs and eight independent service provision ISTs ( table 1 ) will be selected at random from ISTs surveyed in phase 1 of the study. 20 Service users, either already under the care of the 16 ISTs or newly referred, and their caregivers will be identified by IST staff either at first clinical assessment or from the IST services caseloads and asked if they are interested in taking part in the study. Following an expression of interest, the researchers will contact them to provide information about the study and to obtain written or audio-recorded informed consent from those agreeing to undergo further research assessments.…”
Section: Methods and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…The NHS Benchmarking Network (2018) for LD report showed that only 44% of the 54 community LD services that had submitted data had an ISS. Hassiotis et al (2020) in a national cross-sectional survey of 73 intensive support teams (ISTs). identified two models of provision – independent of the main team and enhanced provision within the existing team.…”
Section: Introductionmentioning
confidence: 99%